Chronic suppurative otitis media: a clinico-microbiological menace - Khatoon, Abida; Rizvi, Meher; Sultan, Asfia; Khan, Fatima; Sharma, Mohit; Shukla, Indu; Khan, Haris M. (International Journal of Research in Medical Sciences, 2017)
Background: Chronic Suppurative Otitis Media (CSOM) is an important cause of preventable hearing loss. Global emergence of resistant strains is of great concern. The aim of the present study was to determine the etiology and antibiotic sensitivity pattern of bacterial isolates from CSOM cases with special emphasis on ESBL (Extended Spectrum Beta- Lactamases) and AmpC beta lactamases. Methods: Patients with sign and symptoms suggestive of CSOM, ESBL (Extended Spectrum Beta-Lactamases), AmpC beta lactamases and MBLs (Metallo beta lactamases) were included. Two ear swabs were taken from all the patients and cultured on blood agar and MacConkeyagar. Bacterial identification of isolates was done using standard biochemicals. Antimicrobial susceptibility was performed by Kirby-Bauer's disc diffusion method as per the Clinical Laboratory Standards Institute (CLSI) guidelines using antibiotic discs (HI MEDIA). Results: Out of 130 patients, 110(84.62%) had bacterial growth. The common pathogenic species were Pseudomonas aeruginosa 36(37.89%), Staphylococcus aureus 31(32.63%), Citrobacter koseri 9(9.47%) and Proteus vulgaris 6(6.32%). P. aeruginosa showed maximum sensitivity to colistin (94.4%), polymixin-B (91.3%) and imipenem (91.3%). Gram positive cocci showed maximum sensitivity to vancomycin (99%). MRSA (Methicillin Resistant Staphylococcus aureus) and HLAR (High Level Aminoglycoside Resistance) were detected in 9(29%) S. aureus and 1(50%) Enterococcus faecalis respectively. ESBL and AmpC were detected in 11(18.3%) and 12(20%) Gram negative bacteria, respectively and MBL producer was not detected. Conclusion: P. aeruginosa was found to be the most common isolate in CSOM cases and colistin, polymixin-B and imipenem was found to be most effective antibiotics.